The Effectiveness of Children’s Learning Time in Online Learning System During the Covid 19 Pandemic in Kindergartens - Syamsuardi Saodi; Herlina Herlina; Muhammad Irfan (Universitas Negeri Makassar, 2021)
This study is to determine the effectiveness of children's learning time when the role of the teacher is taken over by the parents as a controller of children's learning at home. This research is a qualitative exploratory research with an inductive approach using social situations involving three elements, namely: place, actor and activity. Respondents in this study involved 15 educational institutions, teachers of study groups aged 4-6 years, parents and students at kindergartens in Makassar City. The data analysis used thematic analysis and was presented in a descriptive form. The results show that the use of the effective learning time during the COVID-19 pandemic had decreased significantly by 200 percent from the average learning time of children per week, from 900 minutes of direct learning to 300 minutes in online learning. The change in effective time is due to the adjustment of the home learning policy, the lack of readiness of schools in implementing online learning systems, the support of teachers and parents, and the availability of school and parent facilities as well as infrastructure related to the implementation of online learning systems.